Assessment of the SEMI energy conversion factor and its application for semiconductor and LCD fabs. (5th July 2017) - Hu, Shih-Cheng; Tsai, Yao-Wen; Fu, Ben-Ran; Chang, Cheng-Kuang
Highlights: Energy conversion factors (ECFs) are needed by designers and operators of fabs. A new ECF calculator can provide factors and allow analysis of energy use. The energy contributions of sub-systems (facilities) in a fab is examined. The applications of this calculator were studied for three high-tech fabs. Abstract: High-tech fabrication plants (called fabs) generally use a lot of energy, for example, yearly energy consumption might reach 215 GWh for a 3.5-generation small/medium-size TFT-LCD panel fab with a monthly yield of 75, 000 pieces and a clean room area of 59, 760 m 2 [1] . The process tools use electricity directly during their operation and also consume energy indirectly through other facilities (such as the exhaust, clean dry air, and process cooling-water systems). The organization Semiconductor Equipment and Materials International (SEMI) issued guidelines (called SEMI S23) for energy, electricity, and production conservation by facility systems. In this study, a calculator was developed to provide the energy conversion factors (ECFs) needed in a fab. The results show that most of the ECF values estimated by the new calculator are very close to the values reported in the SEMI S23-0813, while applying the same operating conditions. Most importantly, with the new calculator, it is possible to understand better the detailed contribution of each variable to the energy consumption of each sub-system in the fab. The new ECF calculator eliminates one drawback of the SEMI S23-0813, the inability to objectively compare results for different industries, or under different operating conditions. The new ECF calculator can be used as a straightforward tool for energy-saving tasks or for new-fab design. Moreover, this new calculator was successfully employed to analyze in detail the energy consumption of three high-tech fabs (for manufacturing semiconductors and LCDs). The ECFs reported in the present study can be considered normalized results because those factors are actually the energy consumption of a sub-system per unit volume flow rate (and unit temperature degree).